DIVIDEN TUNAI DAN KUALITAS LABA (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Periode 2003-2012) - , GALANG PEKERTI UTAMA; , Fuâad Rakhman, S.E., M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objective of this study is to find empirical evidence whether cash dividend is indicative of firmâs earnings quality. This study uses absolute value of discretionary accrual as earnings quality proxy. Sample consists of 127 firms listed in Indonesia Stock Exchange for the year of 2003-2012. The results of the study show that dividend paying status is positively associated with earnings quality. This study also find that firm who increase it dividend has better earnings quality than that of do not incre ase it dividend. Overall, this study concludes that cash dividend is informative about firmâs earnings quality.